Optimization of the Effect of Temperature and Bed Height on Cr (VI) Bioadsorption in Continuous System - Villabona-Ortíz, Angel; Tejada-Tovar, Candelaria; Ruiz-Paternina, Erika; Frías-González, Jesús David; Blanco-García, Gerlyn David (Universidad Pedagógica y Tecnológica de Colombia, 2020)
In the present paper, the residues of the plantain starch extraction process are proposed as an adsorbent to remove Cr (VI) in a continuous fixed bed-system, varying the temperature in 33, 40, 55, 70 y 76 °C and bed height in the range of 15.5, 30, 65, 100, 114.5 mm. The adsorbent material was characterized by Fourier Transform Infrared Spectroscopy (FTIR), Scanning Electron Microscopy (SEM) and X-ray Diffraction Analysis (XRD). The Cr (VI) solution at 100 ppm had contact with the column by gravity, with a flow rate of 0.75 mL/s at the different working conditions. At the end of the process, the residual concentration of the metal was measured by UV-Vis spectroscopy using the standard method for the determination of Cr (VI) in water ASTM D1687-17. From the results, it was established that the bioadsorbent has the presence of hydroxyl, carboxyl and methyl functional groups and that the adsorption process is controlled by electrostatic interactions; the variables evaluated had a significant influence on the process because applying the RSM methodology it was observed that the optimal operating conditions are 81.49 mm of bed height and temperature of 68 ºC. Based on the behavior of the rupture curve, it was found that the bio-material has the potential to be used as a filler in an adsorption column with the purpose of remove Cr (VI).